Characterisation of the join of electric discharge pulse welded ceramics - J.G.P. Binner; P.A. Davis; J.A. Fernie; I.D. Dubovetsku (1995)
A series of sialon, silicon carbide (SC) and lead zirconium titanate (PZT) ceramics joined by an electric discharge pulse-welding process have been examined to provide information on joint characteristics. Techniques used include X-ray diffraction, scanning electron microscopy and energy dispersive X-ray analysis. Results indicate that joints with variable degrees of interfacial contact, interlayer porosity and thermal stress have been produced, depending on the precise conditions used. Titanium was found to provide better wetting characteristics than aluminium when used as an interlayer material.